X-ray dark-field phase-contrast imaging: Origins of the concept to practical implementation and applications. (November 2020) - Ando, Masami; Gupta, Rajiv; Iwakoshi, Akari; Kim, Jong-Ki; Shimao, Daisuke; Sugiyama, Hiroshi; Sunaguchi, Naoki; Yuasa, Tetsuya; Ichihara, Shu
Highlights: Visualizing human soft tissue with very high contrast and excellent high resolution. Availability of 3D information that medical staff can 3-dimensionally diagnose diseased tissue. Feasibility of early diagnosis for finding out disorder of cancer, vessel without contrast agent. Capable of early diagnosis with low level X-ray tomosynthesis for finding out disorder of articular cartilage. Abstract: The basic idea of X-ray dark-field imaging (XDFI), first presented in 2000, was based on the concepts used in an X-ray interferometer. In this article, we review 20 years of developments in our theoretical understanding, scientific instrumentation, and experimental demonstration of XDFI and its applications to medical imaging. We first describe the concepts underlying XDFI that are responsible for imparting phase contrast information in projection X-ray images. We then review the algorithms that can convert these projection phase images into three-dimensional tomographic slices. Various implementations of computed tomography reconstructions algorithms for XDFI data are discussed. The next four sections describe and illustrate potential applications of XDFI in pathology, musculoskeletal imaging, oncologic imaging, and neuroimaging. The sample applications that are presented illustrate potential use scenarios for XDFI in histopathology and other clinical applications. Finally, the last section presents future perspectives and potential technical developments that can make XDFI an even more powerful tool.